Study of anxiety disorders and its association with quality of life in patients of oral cancer - Archanaben Surajprasad Kantak,; Kinjal Bhupendrasinh Chauhan,; Ashokkumar Ukabhai Vala,; Bharat Navinchndra Panchal, (Asian Journal of Medical Sciences, 2022)
Background: Anxiety is a response to a threat that is unknown/known, internal/external, vague, or conflictual, cancer is threatening and so many patients are anxious. Aim and Objectives: The present study was performed to assess the prevalence of anxiety disorders (AD) and quality of life (QoL) and its association in patients of oral cancer. Materials and Methods: There were 62 patients attending cancer OPD of tertiary care center was assessed for cross-sectional, observational, and questionnaire-based study. Patients those diagnosed with oral cancer were included in our study. They were diagnosed for AD by clinical interview using DSM-5 diagnostic criteria. We assessed QoL in patients with oral cancer by scale of Functional Assessment of Cancer Therapy-Head and Neck (FACT-H&N Version 4). Patients were further assessed for demographic details. Statistical analysis was done using SPSS version 15, proportions were compared using Chi–square test, FACT H&N QoL scores were compared by Mann–Whitney U test. P<0.05 was considered to be statistically significant. Results: We found that 17.74% had AD and those patients who were diagnosed of AD have poorer QoL in all domains of FACT H&N QoL. Conclusions: QoL was found to be poor in patients with oral cancer who had diagnosed with AD then those without AD.